Table lands : food in children's literature - Keeling, Kara K.; Pollard, Scott T. (Children's Literature Association series., 2020)
"Food is a signifier of power for both adults and children, a sign of both inclusion and exclusion and of conformity and resistance. Many academic disciplines-from sociology to literary studies-have studied food and its function as a complex social discourse, and the wide variety of approaches to the topic provides multidisciplinary frames for understanding the construction and uses of food in all types of media, including children's literature. Table Lands: Food in Children's Literature is a survey of food's function in children's texts, showing how the sociocultural contexts of food reveal children's agency. Authors Kara K. Keeling and Scott T. Pollard examine texts that vary from historical to contemporary, noncanonical to classics, and Anglo-American to multicultural traditions, including a variety of genres, formats, and audiences: realism, fantasy, cookbooks, picture books, chapter books, YA novels, and film. Table Lands offers a unified approach to studying food in a wide variety of texts for children. Spanning nearly 150 years of children's literature, Keeling and Pollard's analysis covers a selection of texts that show the omnipresence of food in children's literature and culture and how they vary in representations of race, region, and class, due to the impact of these issues on food. Furthermore, they include not only classic children's books, such as Winnie-the-Pooh, but recent award-winning multicultural novels as well as cookbooks and even one film, Pixar's Ratatouille"--